2021
DOI: 10.1186/s13048-021-00776-2
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-mediated transfer of CD44 from high-metastatic ovarian cancer cells promotes migration and invasion of low-metastatic ovarian cancer cells

Abstract: Objective To investigate the detailed roles and mechanisms of tumor-derived exosomes in progression and metastasis of ovarian cancer in vitro. Methods Exosomes were isolated by differential centrifugation method; the morphology, size and biological markers of exosomes were separately defined by transmission electron microscopy, nanoS90 and Western blotting; Trans-well chambers assay was used to assess the ability of migration and invasion of recipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…These data support the hypothesis that ovarian cancer cells utilize extracellular vesicle signaling between cancer cells to propagate chemoresistance. Furthermore, the data obtained are consistent with recent studies that implicate extracellular vesicles in hypoxia-induced metabolic changes within the pre-metastatic milieu [38][39][40] and in the acquisition of chemoresistance [41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…These data support the hypothesis that ovarian cancer cells utilize extracellular vesicle signaling between cancer cells to propagate chemoresistance. Furthermore, the data obtained are consistent with recent studies that implicate extracellular vesicles in hypoxia-induced metabolic changes within the pre-metastatic milieu [38][39][40] and in the acquisition of chemoresistance [41][42][43][44][45][46].…”
Section: Discussionsupporting
confidence: 90%
“…Studies have demonstrated that exosome-mediated transfer of key proteins plays an essential role in ovarian carcinogenesis. 90 , 91 For instance, the migration and invasion of low-metastatic ovarian cancer cells were enhanced due to exosome-involved transfer of CD44 from high-metastatic ovarian cancer cells. 90 Exosomes derived from ovarian cancer cells transported CD44 to human peritoneal mesothelial cells, thus increasing the invasive ability of ovarian cancer.…”
Section: The Role Of Exosome-carried Proteins In Ovarian Cancermentioning
confidence: 99%
“…Fourth, exosomes lack toxicity and immunogenicity (228). It has been evident from various studies (229)(230)(231)(232) that exosomes and their contents have the innate ability to govern cell survival, proliferation, migration, and differentiation in the damaged heart; thereby, reducing the risk of CVD-related deaths.…”
Section: Advantages Of Exosomesmentioning
confidence: 99%